OXTR polymorphism in depression and completed suicide—A study on a large population sample. (March 2017) - Wasilewska, Krystyna; Pawlak, Aleksandra; Kostrzewa, Grażyna; Sobczyk-Kopcioł, Agnieszka; Kaczorowska, Aleksandra; Badowski, Jarosław; Brzozowska, Małgorzata; Drygas, Wojciech; Piwoński, Jerzy; Bielecki, Wojciech; Płoski, Rafał
Highlights: AA males in general population have lower BDI scores. Among male suicide victims, AA individuals have higher blood alcohol concentration. rs53576 has no direct effect either on depression or completed suicide. Abstract: In the light of contradictory results concerning OXTR polymorphism rs53576 and depression, we decided to verify the potential association between the two on 1) a large, ethnically homogenous sample of 1185 individuals who completed the Beck Depression Inventory (BDI), as well as on 2) a sample of 763 suicide victims. In the population sample, AA males showed significantly lower BDI scores (p = 0.005, pcor = 0.030). Exploratory analyses suggested that this effect was limited to a subgroup within 0–9 BDI score range (p = 0.0007, U-Mann Whitney test), whereas no main effect on depressive symptoms (BDI > 9) was found. In the suicide sample no association with rs53576 genotype was present. Exploratory analyses in suicides revealed higher blood alcohol concentration (BAC) among AA than GG/GA males (p = 0.014, U-Mann Whitney test). Our results show that the OXTR rs53576 variant modulates the mood in male individuals and may positively correlate with alcohol intake among male suicides, but is not associated with suicide or depression. The study adds to the growing knowledge on rs53576 genotype characteristics.